Investigasi Potensi Penggunaan Nanofluida Water-CuO untuk Ekstraksi Energi pada Abandoned Geothermal Well - Syaharussajali, Syaharussajali; Suyanto, Suyanto; Wahyuono, Ruri Agung (Gravity : Jurnal Ilmiah Penelitian dan Pembelajaran Fisika, 2024)
Indonesia has a geothermal potential of 24 Gigawatts (GW), making Indonesia the second largest country with geothermal potential. High investment costs are still a challenge in the development of geothermal energy, where the cost of drilling geothermal wells is the most expensive with a cost of more than 50% of the total project cost. One solution to this problem is retrofitting abandoned wells with a closed loop well system (double pipe heat exchanger). Reusing abandoned wells to extract heat energy only costs about a third of the cost of making a new geothermal well. However, the low heat transfer value of this system makes it rarely applied as a power plant. Therefore, the thesis research analyzes the effect of adding CuO nanoparticles in the base fluid (water) of a double pipe well as a solution to improve heat transfer performance. The effect of nanoparticles on closed loop wells is modeled using a CFD simulation approach. The results of the CFD simulation will be used as input in calculating the performance of the Organic Rankine Cycle system which is used to determine the potential for electricity generation. Based on the calculation results, it was obtained that CuO nanoparticles with a concentration of 4%wt had the greatest heat transfer among other nanoparticle variations and this was in line with the power output produced, which was 2045 kW.